New ebooklet: A librarian’s process for building an institutional repository - Stezano, L. (Elsevier, 2016)
Researched and written by Leo Stezano, who recently completed a three-year engagement as Project Manager at the Avery Architecture and Fine Arts Library at Columbia University, the ebooklet provides a handy how-to structure for an institutional repository project and can be adapted to other LIS initiatives.